Managerial accounting in the implementation of deliverology using the example of Ukraine - Andrii Y. Buriachenko; Tetiana V. Zhyber; Tetiana Paientko (Central European Economic Journal (CEEJ), 2020)
The article is devoted towards the application of managerial accounting for deliverology development at the local government level in countries and comparing them to the stage of fiscal decentralisation implementation in Ukraine. The aim of the article is to show how the application of the managerial accounting approach in the public sector can contribute to the introduction of deliverology at the local level using Ukraine as an example. The methodology is based on the application of Difference in Difference method for the implementation of deliverology at the local government level. It has been proved that the use of multi-criteria decision-making methods in the analysis of the performance of budget programmes at the local level will contribute to the improvement of public services delivery. The main contribution of this study is to provide the basis for developing recommendations for the use of a single or uniform standard of electronic databases on regional development indicators and local budgets. This will help to ensure operational control over deviations of actual indicators from planned ones, as well as identify regions where local authorities are using resources inefficiently.
Keywords: M48; R50; R51; 330; managerial accounting; new public management; local budgeting; performance indicators; deliverol-ogy; process-driven problem solving; Difference in Difference method